A human induced pluripotent stem cell‐derived cortical neuron human‐on‐a chip system to study Aβ42 and tau‐induced pathophysiological effects on long‐term potentiation. Issue 1 (27th May 2020) - Caneus, Julbert; Akanda, Nesar; Rumsey, John W.; Guo, Xiufang; Jackson, Max; Long, Christopher J.; Sommerhage, Frank; Georgieva, Sanya; Kanaan, Nicholas M.; Morgan, David; Hickman, James J.
Abstract: Introduction: The quest to identify an effective therapeutic strategy for neurodegenerative diseases, such as mild congitive impairment (MCI) and Alzheimer's disease (AD), suffers from the lack of good human‐based models. Animals represent the most common models used in basic research and drug discovery studies. However, safe and effective compounds identified in animal studies often translate poorly to humans, yielding unsuccessful clinical trials. Methods: A functional in vitro assay based on long‐term potentiation (LTP) was used to demonstrate that exposure to amyloid beta (Aβ42 ) and tau oligomers, or brain extracts from AD transgenic mice led to prominent changes in human induced pluripotent stem cells (hiPSC)‐derived cortical neurons, notably, without cell death. Results: Impaired information processing was demonstrated by treatment of neuron‐MEA (microelectrode array) systems with the oligomers and brain extracts by reducing the effects of LTP induction. These data confirm the neurotoxicity of molecules linked to AD pathology and indicate the utility of this human‐based system to model aspects of AD in vitro and study LTP deficits without loss of viability; a phenotype that more closely models the preclinical or early stage of AD. Discussion: In this study, by combining multiple relevant and important molecular and technical aspects of neuroscience research, we generated a new, fully human in vitro system to model and study AD at the preclinical stage. This system can serve as a novel drug discovery platform to identify compounds that rescue or alleviate the initial neuronal deficits caused by Aβ42 and/or tau oligomers, a main focus of clinical trials.